Fundamentals of Entreprenuership ENT 300 : Casa de Laundry dry cleaning service / Muhammad Ameer Farhan Mohammad Halim … [et al.] - Mohammad Halim, Muhammad Ameer Farhan; A. Rahman, Nur Aqhilah Nazreen; Engku Salim, Engku Sulaikha; Mohd Zainuddin, Nurikmal Farahin (2020)
The following is a proposal of a business plan named Casa de Laundry which is a laundry service which consists of a dry cleaning, carpet cleaning, curtain cleaning, household item, shoe cleaning, and etc. The company is run by five people, the General Manager, the Marketing Manager, the Administration Manager, the Operation Manager, and the Financial Manager with a capital around RM450,000 in the beginning. We want to be a problem solution for consumers as a newly built company, which is why we aim to offer a superb service to our customers by trying our best to meet all the requirements we demand. Before we begin the business, we have done a lot of research, analysis and survey to ensure that the service we provide can satisfy our target customers needs. On the other hand, we also keep an eye on our competitors which are Wash House , WashVille and Pressto Asia to compete healthily and help us to improve every single day. In order to compete with them, improvise and innovate the existing service is principally our objective which will help the business to be different from others. This also will assist the business to operate effectively and efficiently. Casa de Laundry's target is to become the highest satisfaction for our customer. In addition, we offer a variety of services to the community. We are trying to help people to maintain hygiene and eco-friendly to preserve earth nature. We use the best quality of product to keep it eco-friendly and serve the best for our customer. We even created a website, (www.CasadeLaundry.com.my) to help our customers use our services less hassle. “Touch N Go” is the concept we apply to create easier procedures to use our services. Thus, we also provides pickup and delivery services , called Casa de Laundry Samurai. As for Casa de Laundry we are trying to grow a community and notify our customers of our future plan so that we can keep in touch with our customers. However, with our high quality services, affordable price and consistency. So, we can go beyond it and meet the demands, needs and wishes of customers.